Faculty of Pharmacy, UiTM promoting awareness and practice of confidentiality in the management and conduct of meetings / Syahida Fathiah Ahmad Kamal and Dr. Gurmeet Kaur Surindar Singh - Ahmad Kamal, Syahida Fathiah; Surindar Singh, Gurmeet Kaur (Faculty of Pharmacy, 2023)
The Faculty of Pharmacy, Universiti Teknologi MARA (UiTM), Puncak Alam, held a "Briefing on Confidentiality in Management and Conduct of Meetings" via an online platform (Microsoft Teams) on June 13, 2023. Puan Hajah Noriah Mohamed Ali, Chief Deputy Registrar, Governance and Secretariat Division of the University's Registrar's Office, UiTM, conducted the briefing. The purpose of the briefing was to facilitate comprehension and knowledge acquisition regarding preserving confidentiality during meetings, fostering a sense of accountability, and comprehending the procedures involved in managing the process with integrity and transparency. It is hoped that this initiative will enable faculty members to enrich their knowledge and skills in alignment with the guidelines outlined in Public Administration Development Circular No. 2: 1991: Guide to Meeting Management and Managing of Government Committees; Administrative Directives of the Director General of MAMPU No. 6 Year 2014: Guide to Meeting Management and Writing of Meeting Minutes; and Guidelines on Meeting Management and Writing of Minutes of UiTM 1st Edition 2018.